The moderating role of stakeholder involvement in GHRM-GSCM integration: Evidence from Vietnamese logistics firms - Erkan Duzgun; Erhan Atay (Journal of Open Innovation: Technology, Market and Complexity)
This study investigates the moderating role of stakeholder involvement in the integration of Green Human Resource Management (GHRM) and Green Supply Chain Management (GSCM) within Vietnam’s logistics industry. Drawing on survey data collected from 135 participants across 118 logistics firms -resulting in 357 responses- the research analyzes how supplier collaboration and customer engagement influence the relationship between GHRM and GSCM and contribute to improved sustainability performance. The findings reveal that stakeholder involvement significantly strengthens the impact of environmental training and green performance management on both environmental and operational outcomes. Firms that actively engage with their stakeholders and incorporate their feedback into green initiatives tend to achieve more effective implementation and performance gains. However, the study also uncovers several limitations that hinder the adoption of integrated green practices. These include financial constraints, limited technical expertise, and weak legal enforcement, particularly among small and medium-sized enterprises (SMEs), which face greater difficulty in accessing support for sustainability initiatives. Additionally, a lack of awareness and insufficient institutional incentives further constrain green transformations in the sector. By providing empirical insights into both the enabling and inhibiting factors of GHRM-GSCM integration, this study contributes to a more nuanced understanding of sustainable logistics management in emerging markets. The results highlight the importance of developing targeted stakeholder strategies, fostering collaborative environmental training, and improving Vietnam’s regulatory framework to enhance green performance across logistics firms.